Psychometric properties of the Hungarian Visceral Sensitivity Index (VSI-H): insights from two cross-sectional studies on self-reported IBS and gluten-related conditions - Eszter Bertalan; Zsolt Horváth; Panna Gajdos; Tímea Magyaródi; Adrien Rigó (BMC Psychology)
Abstract Background The present study examines the role of gastrointestinal symptom-specific anxiety in gluten-related conditions (e.g., celiac disease, non-coeliac gluten sensitivity) and in irritable bowel syndrome (IBS). The Visceral Sensitivity Index is widely used instrument for assessing gastrointestinal symptom-specific anxiety, originally used among IBS individuals, but it proved applicable to other health conditions characterized with gastrointestinal symptom presence (e.g., inflammatory bowel disease, eating disorders). The coexistence and symptom overlap between IBS and gluten-related conditions may provide a rationale for investigating gastrointestinal symptom-specific anxiety in the latter population. Methods Two cross-sectional studies were conducted; consisting of 308 self-reported IBS individuals (Mage = 36.46; SDage = 11.08) and 341 individuals with self-reported gluten-related disorders (Mage = 34.48; SDage = 12.18). Self-reported questionnaire assessed the level of gastrointestinal symptom-specific anxiety, trait anxiety, negative affectivity, perceived gastrointestinal symptoms in gluten-related conditions, quality of life and well-being. Results The confirmatory factor analyses supported a unidimensional structure of the Hungarian version of the Visceral Sensitivity Index with adequate fit and high internal consistency in both samples. Invariance testing revealed variations in item interpretation, suggesting caution in statistical comparisons of Visceral Sensitivity Index scores. In the IBS sample, gastrointestinal symptom-specific anxiety showed medium-strong correlations with trait anxiety and IBS-specific quality of life, and among individuals with gluten-related conditions, it correlated with negative affectivity, gastrointestinal symptom frequency, and well-being. Among IBS subtypes, individuals with diarrhoea-predominant (IBS-D) and mixed-bowel habit (IBS-M) subtypes showed significantly higher Visceral Sensitivity Index scores compared to those with the unclassified subtype (IBS-U). Conclusions The Hungarian Visceral Sensitivity Index proves reliable and valid for measuring gastrointestinal symptom-specific anxiety in IBS and gluten-related disorders. Thus, its relevance may extend to other conditions with prevalent GI symptoms, potentially linking both the physical and mental aspects of well-being and quality of life in these conditions.